170k views
1 vote
Assume that f is a one-to-one function.

(a) If f(9) = 17, find f^-1(17).
f^-1(17) =

(b) If F^-1(92) = 46, find f(46).
f(46) =

Assume that f is a one-to-one function. (a) If f(9) = 17, find f^-1(17). f^-1(17) = (b-example-1

1 Answer

4 votes

Answer:

a)


f^(-1)(17)=9

b)


f(46)=92

Step-by-step explanation:

Given the one-to-one function;

a)


f(9)=17,

Recall that;


\begin{gathered} \text{if} \\ f\mleft(a\mright)=b \\ f^(-1)(b)=a \end{gathered}

so;


\begin{gathered} \text{If;} \\ f(9)=17, \\ f^(-1)(17)=9 \end{gathered}

b)


\begin{gathered} \text{if} \\ f^(-1)(92)=46 \\ f(46)=92 \end{gathered}

User Villanuevaquelin
by
5.4k points